Using social-cognition models to predict and design interventions to modify consumers' safe food handling behaviour - Mullan, Barbara (Nova Science Publishers, 2010)
Despite the recognised importance of food-safety, a large number of consumers do not practice adequate food-safety in the home. It is estimated that 5.4 million Australians get sick annually from eating contaminated food and that up to 20% of this illness results from consumer food handling behaviour. Therefore utilising social-cognition models of health to predict what social influences and cognitive processes underlie hygienic food handling is vital for determining the motivators for performance of food-safety behaviours. This chapter will review the efficacy of 3 main social-cognition models – the Health Belief Model (Rosenstock, Strecher, & Becker, 1988), the Theory of Planned Behaviour (Ajzen, 1991) and the Health Action Process Approach (Schwarzer, 1992), in predicting food safety behaviours in consumers. Models that successfully predict behaviour can lead to creations of psychosocial interventions to improve food-safety knowledge, attitudes and behaviours. Past behaviour was found to increase the prediction of both intentions and behaviour suggesting that food-safety behaviours are habitual. A number of other studies which have extended the Theory of Planned Behaviour will also be outlined. For example, a recent study investigated the role of habit as distinct from past behaviour, as habit is likely to be modifiable (Harris & Mullan, 2009) and additional research investigated the role of self-regulation (Fulham & Mullan, 2009). This research has led to interventions that aim to change behaviour by increasing significant social-cognitive variables such as perceived behavioural control and creating implementation intentions to bridge the relationship from intention to behaviour and a recent systematic review of interventions into food hygiene (Milton & Mullan, in press) investigated the components of successful interventions. Based on this review and the detailed theoretical frame work outlined previously a number of experiments to improve food hygiene will be explored. The chapter will also review the theory-based interventions that aim to change food-safety behaviours, attitudes and knowledge and discuss the future direction of food safety research.